Normalization of NEXRAD antenna gain for overlapping radars - Kasparis, Takis; Boustany, Sami; Jones, Linwood W. (My University, 1999)
An improved method that uses low-elevation radar reflectivity scans of precipitation events taken asynchronously in time was developed and applied to two NEXRAD radars located in Melbourne (KMLB) and Miami (KAMX), Florida. Reflectivity data analyzed for two precipitation events indicate consistent, time-invariant dBz biases.
Keywords: Meteorological satellites; Algorithms; Radar--Antennas; Radar--Measurement; Doppler radar